Vibration reduction analyses using individual blade pitch controls for lift-offset rotors - Park, J.S.; Kim, D.H.; Chae, S.; Lee, Y.L.; Go, J.I. (My University, 2018)
This work attempts to reduce the hub vibratory loads of a lift-offset rotor using IBC (Individual Blade pitch Control) in high-speed forward flight. As a lift-offset rotor for the present study, the rigid coaxial rotor of XH-59A compound helicopter is considered, and CAMRAD II is used to predict the hub vibration and rotor performance. Using the IBC with a single harmonic input at 200 knots, the vibration index of the XH-59A rotor is minimized by about 62% when the 3/rev actuation frequency is applied with the IBC amplitude of 1 and control phase angle of 270 (3P/1/270); however, the rotor effective lift-to-drag ratio is reduced by 3.43%. When the 2/rev actuation frequency with the amplitude of 2 and control phase angle of 270 (2P/2/270) and the 3/rev actuation frequency using the magnitude of 1 and control phase angle of 210 (3P/1/210) are used in combination for the IBC with multiple harmonic inputs, the vibration index is reduced by about 62%, while the rotor effective lift-to-drag ratio increases by 0.37% at a flight speed of 200 knots. This study shows that the hub vibration of the lift-offset rotor in high-speed flight can be reduced significantly but the rotor performance increases slightly, using the IBC with multiple harmonic inputs.